Understanding long term impact of traumatic brain injury (TBI) survivors during recovery following discharge from the intensive care units (ICU) in Malaysian hospitals - Mohamed Ludin, Salizar; Abdul Rashid, Nor'ain (2016)
Introduction: Traumatic brain injury (TBI) is the number one cause of mortality and disability in young adults in western societies, while head injury (including TBI) is reported as one of the top three most common diagnoses (for 9 years) leading to Intensive Care Unit (ICU) admission in Malaysian hospitals. Medical advances have improved the survival rate after severe TBI, but survivors may face a lifetime disability. Despite international studies concluded that subjects with moderate and severe TBI shows physical and functional improvement but remain with cognitive and psycho-social problem throughout the recovery, TBI survivors’ long term outcome of in Malaysia is unknown.